ANALISIS NILAI TAMBAH BROKOLI KEMASAN CV. YAN’S FRUITS AND VEGETABLE DI KECAMATAN LEMBANG BANDUNG BARAT - Clara Yolandika; Rita Nurmalina; Suharno Suharno (Politeknik Negeri Lampung, 2017)
This study aimed to analyze broccoli added value in CV. Yan’s Fruits and Vegetable. The study was conducted at CV. Yan's Fruits and Vegetable from July to August 2016. This study used primary and secondary data. The research sample was taken purposively consisting of 30 farmers of CV. Yan’s Fruits and Vegetable partners. The method used to analyse supply chain condition was Hayami Method to analyze broccoli added value in CV. Yan’s Fruits and Vegetable. The results showed that the marketing condition of broccoli in Cibodas Village is already good. They already have a good integration among members of the supply chain. Integrated quality and optimization of the supply chain have been the targets of any relevant actors in the broccoli supply chain so it can create added value for broccoli. From the added value calculation of packaged broccoli, it can be concluded that it has added value of 36.92 percent. Keywords: Broccoli, packing, Value-Added